Profile of small interfering RNAs from cotton plants infected with the polerovirus Cotton leafroll dwarf virus - Silva, Tatiane F (BioMed Central, 2011)
BACKGROUND: In response to infection, viral genomes are processed by Dicer-like (DCL) ribonuclease proteins into viral small RNAs (vsRNAs) of discrete sizes. vsRNAs are then used as guides for silencing the viral genome. The profile of vsRNAs produced during the infection process has been extensively studied for some groups of viruses. However, nothing is known about the vsRNAs produced during infections of members of the economically important family Luteoviridae, a group of phloem-restricted viruses. Here, we report the characterization of a population of vsRNAs from cotton plants infected with Cotton leafroll dwarf virus (CLRDV), a member of the genus Polerovirus, family Luteoviridae. RESULTS: Deep sequencing of small RNAs (sRNAs) from leaves of CLRDV-infected cotton plants revealed that the vsRNAs were 21- to 24-nucleotides (nt) long and that their sequences matched the viral genome, with higher frequencies of matches in the 3- region. There were equivalent amounts of sense and antisense vsRNAs, and the 22-nt class of small RNAs was predominant. During infection, cotton Dcl transcripts appeared to be up-regulated, while Dcl2 appeared to be down-regulated. CONCLUSIONS: This is the first report on the profile of sRNAs in a plant infected with a virus from the family Luteoviridae. Our sequence data strongly suggest that virus-derived double-stranded RNA functions as one of the main precursors of vsRNAs. Judging by the profiled size classes, all cotton DCLs might be working to silence the virus. The possible causes for the unexpectedly high accumulation of 22-nt vsRNAs are discussed. CLRDV is the causal agent of Cotton blue disease, which occurs worldwide. Our results are an important contribution for understanding the molecular mechanisms involved in this and related diseases.